The Quality Control of Micro- and Nanomedicines: Compliance with Regulatory Guidelines - Lu Li; Wei Wu; Jian Le; Yi Lu (Pharmaceutical Fronts)
Carrier-based micro- and nanomedicines, such as microspheres, liposomes, and micelles, offer enhanced benefits over traditional medications, including improved bioavailability, targeted delivery, and reduced toxicity. Unlike conventional drugs, the particle size, shape, surface charge, and surface chemical properties of carrier-based micro/nanomedicines are key factors in determining their efficacy and toxicity. Even minor deviations in their preparation can significantly impact their in vivo performance. Therefore, the quality control of carrier-based micro/nanomedicines is more complicated than for conventional drugs. Regulatory authorities from the United States and China have established guidelines for their quality assessment. These guidelines categorize quality indicators into basic characteristics such as pH, viscosity, microbial limits, and nano-specific characteristics, including particle size, morphology, and stability. This review summarizes the significance and methodologies for evaluating these characteristics based on pharmacopeias and guidelines, emphasizing the distinct quality control requirements for different types of carrier-based micro- and nanomedicines.